Therapeutic communities and group analysis. Issue 2 (12th June 2017) - Lees, Jan; Haigh, Rex; Tucker, Sarah
Abstract : Purpose: The purpose of this paper is to highlight theoretical and clinical similarities between therapeutic communities (TCs) and group analysis (GA). Design/methodology/approach: Literature review shows comparison of TC and group-analytic concepts with illustrative case material. Findings: Findings reveal many similarities between TCs and GA, but also significant divergences, particularly in practice. Practical implications: This paper provides theoretical basis for TC practice, and highlights the need for greater theorising of TC practice. Social implications: This paper highlights the importance of group-based treatment approaches in mental health. Originality/value: This is the first paper to review the relevant literature and compare theory and practice in TCs and GA, highlighting their common roots in the Northfields Experiments in the Second World War.